2008
DOI: 10.1017/s1047951108003107
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of echocardiographic criterions for the diagnosis of carditis in acute rheumatic fever

Abstract: Using our echocardiographic criterions, it is possible to make a precise diagnosis of carditis or subclinical valvitis. Hence, echocardiography should, in future, be included as a major criterion in the Jones' system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 14 publications
(25 reference statements)
3
44
0
Order By: Relevance
“…(15) Normal valve thickness was shown to be agerelated by Sahasakul et al in a well-designed postmortem study (level 2++ evidence), and correlation between surgical and echocardiographic measurements seems to be good if harmonic imaging is not used, as this modality increases apparent tissue thickness. (10,(15)(16)(17)(18)(19) On the basis of data from a study of 280 healthy children in New Zealand. (20) the normal echocardiographic thickness of the anterior MV leaflet (AMVL) in school-aged children is 1.12-2.92 mm (mean±SD of 2.02±2mm) (level 2++ evidence).…”
Section: Discussionmentioning
confidence: 99%
“…(15) Normal valve thickness was shown to be agerelated by Sahasakul et al in a well-designed postmortem study (level 2++ evidence), and correlation between surgical and echocardiographic measurements seems to be good if harmonic imaging is not used, as this modality increases apparent tissue thickness. (10,(15)(16)(17)(18)(19) On the basis of data from a study of 280 healthy children in New Zealand. (20) the normal echocardiographic thickness of the anterior MV leaflet (AMVL) in school-aged children is 1.12-2.92 mm (mean±SD of 2.02±2mm) (level 2++ evidence).…”
Section: Discussionmentioning
confidence: 99%
“…(8,9,21) Chordal thickening in the context of acute carditis suggests recurrence of acute rheumatic fever in patients with established rheumatic heart valve disease. (22) Mild mitral regurgitation present during the acute phase usually resolves weeks to months after, while patients with moderate-to-severe carditis have persistent mitral regurgitation. In most cases, the left ventricle is dilated with preserved or increased fractional shortening; however, a variable degree of ventricular dysfunction may occur in very advanced cases in African patients.…”
Section: Echocardiographymentioning
confidence: 99%
“…A study of 333 patients with possible clinical carditis showed that the Jones criteria and echocardiography were concordant (both positive or both negative) 83% of the time. 42 Controversy arises in the group of patients with so-called subclinical carditis or silent carditis in whom the clinical examination is negative but echocardiography reveals features suggestive of valvulitis. 43,44 In the Utah outbreak, carditis could only be detected by echocardiography in 14 of 74 (19%) of patients.…”
Section: Accuracy Of Echocardiographymentioning
confidence: 99%